Mortality salience and helping intentions: mediating role of search for meaning and moderating role of negotiable fate - Chang, Baorui; Cheng, Jiaxin; Fang, Jiandong; Lyu, Zhaohua (Frontiers in Psychiatry, 2025)
IntroductionThis study explores the “altruism born of suffering” hypothesis, which suggests that adversity motivates individuals to help others, potentially mediated by their search for meaning. Grounded in terror management theory, it investigates how mortality salience influences helping intentions and examines the moderating role of negotiable fate, a key destiny view in Chinese culture. Compared to conquering fate and fatalism, negotiable fate is hypothesized to enhance helping intentions when mortality is salient.MethodsTwo experimental studies were conducted. Study 1 tested the mediating role of search for meaning in the relationship between mortality salience and helping intentions. Study 2 examined whether negotiable fate beliefs moderate this relationship, specifically strengthening the effect of mortality salience on helping intentions.ResultsStudy 1 found that mortality salience positively predicts helping intentions, fully mediated by search for meaning. Study 2 showed that negotiable fate moderates this relationship, with mortality salience significantly enhancing helping intentions when negotiable fate is salient. These findings highlight the role of negotiable fate in shaping prosocial behavior under mortality reminders.DiscussionThe results emphasize the importance of fostering search for meaning and negotiable fate beliefs to promote helping intentions when mortality is salient. This research advances understanding of how cultural beliefs and existential concerns interact to drive altruistic behavior, suggesting practical interventions to encourage prosocial actions in mortality-salient contexts.